Integrative techno-economic and environmental assessment for green H2 production by alkaline water electrolysis based on experimental data. Issue 6 (December 2021) - Lee, Boreum; Cho, Hyun-Seok; Kim, Heehyang; Lim, Dongjun; Cho, Wonchul; Kim, Chang-Hee; Lim, Hankwon
Abstract: Alkaline water electrolysis has been in the spotlight for green H2 production using electricity generated from renewable energy because of its high technology readiness level and low investment. However, commercialization of alkaline water electrolysis is challenging because of the low current density. Therefore, a techno-economic and environmental assessment was conducted for green H2 production by alkaline water electrolysis with experimental data from the advanced alkaline water electrolysis system of the Korea Institute of Energy Research (KIER) to identify the potential of this technology. Based on techno-economic analysis results, the stack cost and unit electricity price must be below 0.035 kWh −1 and 406 kW −1, respectively, to make this technology cost-competitive compared to the conventional H2 production method (< 2 kgH2 −1 ). Furthermore, CO2 emissions of 30.7, 17.4, 7.04, and 3.12 kgCO2-eq kgH2 −1 were obtained for the current, 2030, 2050, and renewable Korean electricity mix scenarios, respectively, indicating that both scenarios (Korean electricity mix in 2050 and renewable) have lower CO2 emissions than the conventional H2 production method (11.5 kgCO2-eq kgH2 −1 ). In addition, environmental impact reductions of 89.8%, 83.6%, 65.9%, and 91.0% for CO2 emissions, stratospheric ozone depletion, fine particulate matter formation, and fossil resource scarcity, respectively, were obtained for the renewable scenario compared to the current Korean electricity mix. Therefore, the electricity source has significant effects on the economic feasibility and environmental impacts for green H2 production. Graphical Abstract: ga1 Highlights: TEA was performed to calculate unit H2 production based on experimental data. Life cycle assessment was conducted to evaluate environmental impacts for green H2 production. Economic and environmental guidelines can be provided.